Prompt corrective action in banking : 10 years later - Kaufman, George G. (Amsterdam ; London : JAI, 2002)
A storehouse of knowledge on improving the performance of banking systems and should prove useful to researchers, practioners, and policy-makers both in evaluating extant regulatory structures and in designing new or modified structures.
Papers presented at special sessions at the annual meetings of the Western Economic Association in Seattle, Washington in July 2002.
Includes bibliographical references.
oif 27/01/15
Loan
Keywords: Banks and banking; Banking law; Banks and banking -- State supervision; Financial services industry